Respuesta :

Answer:

X= 1

Step-by-step explanation:

y = 5 - 3x

5x - 4y = -3

you substitute for y since you know what y equals.

so, it will then be

5x -4(5 -3x) = -3

you then multiply -4 by everything in the parenthesis

so then it will be

5x - 20 + 12x = -3

Then combine like terms

5x + 12x = 17x

then the new equation is

17x -20 = -3

the next step is to and 20 to both sides since it is negative you do the opposite.

17x - 20 = -3

     + 20     +20

17x = 17 divide 17 by both sides sice 17 is being multiplied by x you do the opposite and divide and you get 1.

so, X = 1